The Semantic Function of Giongo and Gitaigo in Buiding the Atmosphere of the Match in the Manga HAIKYUU!! - Nabilah Juan Novia; Parastuti; Ina Ika Pratita; Yovinza Bethvine Sopaheluwakan (Universitas Negeri Padang, 2026)
Onomatopoeia is a distinctive linguistic feature of the Japanese language that is widely used in manga to represent specific sounds, movements, emotions, and atmospheres. This study aims to describe the types of onomatopoeia and analyze their role in creating the atmosphere of matches in the manga Haikyuu!! by Haruichi Furudate, specifically the match between Karasuno and Aoba Johsai. The study employs a qualitative descriptive approach with a semantic analysis. Research data was collected from Haikyuu!! manga volume 16, chapters 136–144, and volume 17, chapters 145–147. Data collection was conducted through observation and note-taking, while data analysis utilized the matching and categorization methods. The results of the study indicate that onomatopoeia and gitaigo not only function as sound mimics but also as visual linguistic strategies that build the intensity of the match, emotional tension, the rhythm of the game, and the reader’s focus on specific scenes. The use of onomatopoeia such as 「ドン」(don), 「バシッ」(bashi), and 「ドッドッ」(doddot) demonstrates the integration of linguistic and visual elements in creating an immersive reading experience. This study demonstrates that onomatopoeia in sports manga plays a significant semantic and narrative role in building the atmosphere of a match in a dramatic and communicative manner.